The moral development in Stoic oikeiôsis and Wang Yang-ming's 'wan wu yi ti'. Issue 2 (3rd April 2017) - Yu, Jiangxia
ABSTRACT: The Neo-Confucian notion of wan wu yi ti 万物一体 ('form one body') and Stoic oikeiôsis ('appropriation') both come up with a motivational basis for the expansion of concern, but one of the toughest problems in them is how to elaborate on selfhood and self–other relation in moral development. This paper takes a comparative view of Hierocles' fragments and a few other relevant Stoic texts and Wang Yang-ming's Inquiry on the Great Learning, and argues that doing so helps eliminate some confusions concerning selfhood and self–other relation. My claim is that  the concept of the Stoic oikeiôsis and the concept of Wang's ' wan wu yi ti ' have different ideas on selfhood and the self–other relation while showing similarities in basing the ideal of self-development on the original unity between self and world.